Pengaruh Pengetahuan Produk, Label Halal Dan Kesadaran Merek Terhadap Keputusan Pembelian Best Fried Chicken (BFC) Restara Batanghari Melalui Rekomendasi Kelompok Sebagai Variabel Moderating - Tri Pungki Astuti; Nina Lelawati; Yateno (Jurnal Manajemen DIVERSIFIKASI, 2025)
This study aims to determine whether product knowledge, halal labels, brand awareness influence purchasing decisions for BFC Restar Batanghari. To find out whether moderation between group recommendations on brand awareness influences the purchasing decision of BFC Restar Batanghari. This research is a quantitative study using a sample of 68 samples. The objects in this study are halal labels, brand awareness, purchasing decisions and group recommendations. This research was conducted at BFC Restara Batanghari which is addressed at Jl. Raya Batanghari, Banar Joyo, Kec. Batanghari, East Lampung. Data collection using questionnaires distributed to research samples. Data analysis using Moderated Anaysis Regression analysis. The results showed that product knowledge had a significant and significant effect on purchasing decisions, the Halal Label had a significant effect on purchasing decisions for BFC Restar Batanghari consumers. Brand awareness can influence purchasing decisions. In this case, brand awareness that has an influence is on the aspect of brand superiority and that which is less influential is showing the brand. the effect of product knowledge on purchasing decisions is not moderated by group recommendation variables. The effect of the halal label on purchasing decisions is moderated by the group recommendation variable which is quite strong. Group recommendation moderation does not affect the relationship between brand awareness and purchasing decisions.